Minimally invasive CT-guiding excision of benign bone tumours - Sluis-Cremer, Timothy Richard (Division of Orthopaedic Surgery, 2019)
Background: The management of osteoid osteoma (OO) and other small primary benign lesions of bone has evolved over the past 50 years from open surgery with wide resection margins to less invasive surgical techniques such as image guided intralesional excision and percutaneous radiofrequency ablation. We aim to evaluate the outcomes of patients treated with computerised tomography (CT guided) intralesional excision and bone grafting of small benign lesions of bone. Method: A retrospective folder review of patients treated in a large academic hospital in Cape Town, South Africa, between March 2012 and May 2016 was performed. Patient demographics, details of presentation, clinical information and outcome following treatment were analysed descriptively. Pre-operative diagnosis based on radiological examination was compared with histological diagnosis. Result: Eleven patients (5 male) with a median age of 16 years (range 5-33) were included. Pain was the most common presenting feature. A histological diagnosis of OO was confirmed in 5 of 9 patients with a suspected diagnosis of OO preoperatively. Of the 4 patients whose diagnosis changed after the procedure the diagnoses included a benign spindle cell lesion, a benign fibrous histiocytoma, subacute osteitis and an osteochondral defect with geode cyst formation. Of the 2 patients where OO was not suspected preoperatively, chondroblastoma was confirmed in one while a benign spindle cell lesion was reported in the other. Overall histological yield was thus 100%. There were no complications or repeat procedures at a median follow up of 42 months (range 30-52 months). Conclusion: CT guided intralesional curettage is a safe and minimally invasive technique. This is especially useful in less accessible regions of the skeleton as it provides a means of accurately locating the lesion with minimal risk of complications and morbidity to the patient. We consider this to be the optimal method of treatment in our setting as it provides high success rates, few complications and a histological diagnosis without the need for any additional and expensive equipment.